2020
DOI: 10.1002/cam4.3518
|View full text |Cite
|
Sign up to set email alerts
|

A decision analysis comparing three strategies for peritoneal lavage cytology testing in staging of gastric cancer in China

Abstract: Background Positive peritoneal cytology (PCY) indicates metastasis (M1) in gastric cancer (GC) patients; both the American and Chinese guidelines recommend laparoscopic peritoneal lavage (LPL) for cytology. However, relatively high costs impair the widespread use of LPL in some resource‐limited regions in China, and the cost‐effectiveness of PCY testing remains unclear. Therefore, we performed a decision analysis to evaluate the cost‐effectiveness of PCY testing by comparing the guideline‐recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…We have not reported the cost of SL in this study but others have reported this ranging between $20,000 and $100,000 per quality-adjusted life year. 22 , 23 Indeed, one cost-effectiveness study from Li et al stresses the importance of performing SL in gastric cancer patients where the probability of metastatic disease is predicted to be high, around 31.5%. 22 This is a good example of where a score such as the one reported here would be useful.…”
Section: Discussionmentioning
confidence: 99%
“…We have not reported the cost of SL in this study but others have reported this ranging between $20,000 and $100,000 per quality-adjusted life year. 22 , 23 Indeed, one cost-effectiveness study from Li et al stresses the importance of performing SL in gastric cancer patients where the probability of metastatic disease is predicted to be high, around 31.5%. 22 This is a good example of where a score such as the one reported here would be useful.…”
Section: Discussionmentioning
confidence: 99%